SITUATION OF THE SPORTS EQUIPMENT MARKET - Harangi-Rákos, Mónika; Nagy, Adrián Szilárd; Pfau, Christa; Müller, Anetta; Szabados, György Norbert; Bácsné Bába, Éva (Acta Carolus Robertus, 2020)
The aim of our article is to present the historical development of the different sports and to analyse the changes of the production of the different sports equipments. As the rules and regulations of the different sports have been indited since the 19th century, the rulebooks of several sports have been also formulated and published. In these rulebooks the exact and strict standards have been created in order to regulate the characteristics of the sports equipments. Economic, social, and familiar circumstances also have effect on the spread of the different sports and on the sporting activity of the people. The production and commerce of the sports equipments represents an important part of the globally increasing sports economics and sports industry. The sports equipments market of the European Union has a great tradition. The importance of the different sports in the Member States of the European Union is distinct and some important sectoral differences can be described between the import and the export of the sports equipments on the level of the European Union. The boats and the water sports tools represent about two third of the EU-level sports equipments export. In case of the sports equipments import we cannot find this kind of centralization.